Common fungus at an uncommon site - Gupta, Alpana; Pathak, Abhishek (International Journal of Advances in Medicine, 2017)
Dermatophytes frequently cause fungal infections limited to the hair, stratum corenum and nails. However, deep dermatophytosis infecting dermis, subcutis and internal visceral organ caused by T. rubrum is a rare clinical entity. To highlight this rare infection, we present a case of swelling in lower limb caused by subcutaneous infection by deep dermatophytes in an elderly individual.